2022
DOI: 10.3390/s22249946
|View full text |Cite
|
Sign up to set email alerts
|

Use of Robot-Assisted Gait Training in Pediatric Patients with Cerebral Palsy in an Inpatient Setting—A Randomized Controlled Trial

Abstract: Robot-assisted gait training (RAGT) provides a task-based support of walking using exoskeletons. Evidence shows moderate, but positive effects in the therapy of patients with cerebral palsy (CP). This study investigates the impact of RAGT on walking speed and gait parameters in pediatric CP patients. Thirty subjects (male = 23; female = 7), with a mean age of 13.0 ± 2.5 (9–17) years, and with spastic CP, were recruited. The intervention group (n = 15) underwent six 20-minute RAGT sessions with the Hybrid Assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The latest research shows that combining RAGT and routine rehabilitation treatment can significantly improve the 6MWT test scores of children with CP compared to routine rehabilitation treatment alone [ 38 ], which is consistent with the results of this study. However, some studies on RAGT have also indicated that the combination of RAGT and routine rehabilitation treatment does not have an advantage in improving the performance of 6MWT compared to routine rehabilitation treatment alone [ 39 ]. Nonetheless, the types of RAGT devices used in the 6MWT tests, including those in this study, vary.…”
Section: Discussionmentioning
confidence: 99%
“…The latest research shows that combining RAGT and routine rehabilitation treatment can significantly improve the 6MWT test scores of children with CP compared to routine rehabilitation treatment alone [ 38 ], which is consistent with the results of this study. However, some studies on RAGT have also indicated that the combination of RAGT and routine rehabilitation treatment does not have an advantage in improving the performance of 6MWT compared to routine rehabilitation treatment alone [ 39 ]. Nonetheless, the types of RAGT devices used in the 6MWT tests, including those in this study, vary.…”
Section: Discussionmentioning
confidence: 99%
“…Study quality assessment classifies randomized trials of four [9][10][11][12] as low risk and three as medium risk. Among the non-randomized studies, eight studies [16][17][18][19][20][21][22][23] were rated as low risk and two papers [24,25] as medium risk.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The meta-analyses included 17 studies. Ten studies analyzed gait speed using the 6MWT (10,11,13,15,16,(19)(20)(21)26,27). Ten articles analyzed the GMFM total [9,12,15,17,18,21,23,25], and the D and E dimensions of the GMFM were presented in eight papers [9,10,12,13,15,17,19,23].…”
Section: Quantitative Analysismentioning
confidence: 99%
“…It increases the ROM in muscles and improves the fine movements of fingers to master the obstacles posed by daily activities. A hybrid robot-assisted limb is a rigid exoskeleton device that provides little action [ 22 ]. Robomorphism is the designed robotic equipment for developing an active lower limb.…”
Section: Reviewmentioning
confidence: 99%